2018
DOI: 10.1103/physrevlett.121.218101
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Energetics of Molecular Motor Kinesin

Abstract: Nonequilibrium energetics of single molecule translational motor kinesin was investigated by measuring heat dissipation from the violation of the fluctuation-response relation of a probe attached to the motor using optical tweezers. The sum of the dissipation and work did not amount to the input free energy change, indicating large hidden dissipation exists. Possible sources of the hidden dissipation were explored by analyzing the Langevin dynamics of the probe, which incorporates the two-state Markov stepper … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
147
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(153 citation statements)
references
References 74 publications
6
147
0
Order By: Relevance
“…[42], where it was shown that even tagged fluid particles closely follow BBO dynamics, the present results are germane to temperature and pressure control algorithms in molecular dynamics simulations, especially as extended phase space approaches show promise in improving the kinetic consistency of thermostats [43,44]. Indeed, such approaches can be brought to bear on the question of stochastic transport efficiency of linear molecular motors like kinesin [45][46][47], with the possibility to incorporate viscoelastic fluid properties [22, 48? , 49].…”
mentioning
confidence: 87%
“…[42], where it was shown that even tagged fluid particles closely follow BBO dynamics, the present results are germane to temperature and pressure control algorithms in molecular dynamics simulations, especially as extended phase space approaches show promise in improving the kinetic consistency of thermostats [43,44]. Indeed, such approaches can be brought to bear on the question of stochastic transport efficiency of linear molecular motors like kinesin [45][46][47], with the possibility to incorporate viscoelastic fluid properties [22, 48? , 49].…”
mentioning
confidence: 87%
“…by coarse-graining in time. The expression (21) is consistent with the multiplicative Langevin (13). Although we do not know the procedure to derive (21), we know it is appropriate from the numerical examination shown in Figs.…”
Section: Relation Betweenmentioning
confidence: 54%
“…Its nonequilibrium version is presented in textbooks and has been studied during the past few decades [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. We numerically identify a multiplicative Langevin equation (13) that reproduces the cumulants of long-time displacement of this nonequilibrium Brownian motion at least up to the third order. The multiplicative Langevin equation contains a linearly velocity-dependent friction coefficient, which can never appear in equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule experiments are a powerful toolbox to study functional dynamics of biomolecular motors by visualizing their motions. Mechanochemical coupling mechanisms of F1-ATPase (1)(2)(3)(4)(5), myosin (6,7) and kinesin (8)(9)(10), typical motors driven by adenosine triphosphate (ATP), have been revealed by various single-molecule techniques. Recently, processive cellulase and chitinase have been cast new light as a different type of biomolecular motors that use hydrolysis energy of polysaccharides for their unidirectional movements by high-speed atomic force microscopy (11,12) and highprecision single-particle tracking (13).…”
Section: Introductionmentioning
confidence: 99%